BMS635: Microbial Biotechnology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course provides an overview of how microbes (e.g., bacteria, viruses and yeast) are manipulated to solve practical problems through biotechnology. Topics include basics in microbial life, ecology and metabolism, methods used in microbial technology, industrial microbiology, microbes in drug development, interactions between microbes, plants and animals; food microbiology, the gut microbiota, metagenomics and others